Prevalence and Histopathological Characteristics of KCNJ5 Mutant Aldosterone-Producing Adenomas in a Multi-Ethnic Malaysian Cohort - Mohideen, Syahirah Kaja; Mustangin, Muaatamarulain; Kamaruddin, Nor Azmi; Muhammad, Rohaizak; Jamal, A. Rahman A.; Sukor, Norlela; Tan, Geok Chin; Azizan, Elena Aisha (Frontiers in Endocrinology, 2019)
Studies on excised adrenals from primary aldosteronism patients have found somatic mutations in KCNJ5 frequently cause excess aldosterone production in the culprit aldosterone-producing adenoma (APA). KCNJ5 mutant APAs were reported to be peculiarly overrepresented among young females and in Oriental cohorts, compared to their older male or Caucasian counterparts. These larger APAs were also reported to have similarities with the zona fasciculata (ZF) in the adrenal both from steroid production profile and morphology of cell. We therefore aimed to corroborate these findings through characterizing the APAs from a multi-ethnic Malaysian cohort. The prevalence of KCNJ5 mutations was estimated through targeted DNA sequencing of KCNJ5 in fifty-four APAs. Confirmation of APA sample acquisition was performed by CYP11B2 immunohistochemistry (IHC) staining. ZF steroid production profile was based on the ZF enzyme CYP17A1 IHC staining and ZF cell morphology was based on high cytoplasm to nucleus ratio. Seventeen (31.5%) APAs studied harboured a KCNJ5 mutation. No female over-representation was seen in this cohort though females were found to have higher expression of CYP11B2 than males (p=0.009; Mann-Whitney U test). Age at adrenalectomy correlated negatively with the percentage of ZF-like cells in the APA (p=0.01; Spearman’s rho) but not with KCNJ5 genotype. KCNJ5 mutant APAs had high percentage of ZF-like cells (and high CYP17A1 expression) but so did the wild-type APAs. In summary, prevalence of KCNJ5 mutant APAs in this cohort was similar to other Caucasian cohorts however over-representation of females did not occur which is similar to some studies in Oriental cohorts.